A theoretical model for gas-contributed thermal conductivity in nanoporous aerogels. (July 2019) - Guo, J.F.; Tang, G.H.
Highlights: We study two different coupling effects in solid-gas coupling heat transfer in aerogel. We propose an analytical model to calculate the coupling thermal conductivity in aerogel. The present model can predict well gas-solid coupling thermal conductivity of aerogel. The influence mechanism of the solid-gas coupling effects in aerogel is discussed. Abstract: A theoretical model for gas-contributed thermal conductivity in aerogel is proposed by considering the coupling effects of both the local solid-gas interaction (heat crossing particles and adjacent gaseous pore) and the thermal-bridge interaction (heat crossing adjacent particles and the gas confined in the gap). The predictions of present model demonstrate a good agreement with experimental data of aerogels with different microstructures and thermophysical properties, exhibiting its good potential of application. The proposed model is then employed to investigate the influence mechanism of the above two solid-gas coupling effects in aerogels. It is shown that the coupling effect of local solid-gas interaction is in a dominant position, while the coupling effect of thermal-bridge interaction becomes noticeable and should not be neglected when the pressure exceeds about 1 atm. The effects of porosity, particle size and thermal conductivity of particles are also examined according to the present model, which could provide guidance for improving heat-insulating capacity of aerogels in engineering.